(untitled) (MAUSAM, 2014)
Trend analysis of the climate variables at different locations (Kanpur, Hyderabad, Bangalore, Pusa, Pantnagar, Parbhani, Varanasi and Pune) in India were studied. These locations are very important for growing of pulses especially pigeonpea. Trend in these locations were analyzed for the maximum temperature (MaxT), minimum temperature (MinT), rainfall (RF) and bright sunshine hours (BSH) on seasonal (summer, kharif or rainy season and rabi or post-rainy season), monthly (January to December), and weekly (1-52 standard meteorological week) time scales for the period 1970-2010. Significant trends were identified using the Mann-Kendall test and the Sen’s slope estimator. Maximum and minimum temperature series showed a rising trend at most of the stations. Some stations located in the north and northeastern India showed a falling trend in temperature. At most of the stations in the south, central and western parts of India a rising trend was found in various climatic variables except rainfall. Most of the data used in trend analysis pertained to the stations located in urban areas considered as heat islands.